RENCANA PELAKSANAAN PEMBELAJARAN RPP DAN MODUL AJAR - Cantika; Nur Resky Al Hijrah Syam; Siti Nurjannah; Takdirmin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Teachers play a crucial role in designing effective learning to optimally achieve learning objectives. Lesson Implementation Plans (RPPs) and open modules are among the tools used in lesson planning. RPPs serve as guidelines for teachers in systematically organizing learning activities, while open modules contain objectives, materials, methods, and assessments tailored to student needs. Curriculum developments in Indonesia, particularly the implementation of the Independent Curriculum, encourage teachers to be more creative and innovative in developing learning materials. Learning modules are designed to enhance learning materials that are more flexible, contextual, and student-centered. Through open modules, the learning process is expected to enhance critical thinking skills, creativity, collaboration, and student learning independence. However, the implementation of RPPs and open modules still faces various challenges. Some frequently encountered obstacles include teachers' lack of understanding regarding developing learning materials that are appropriate to student characteristics, limited time for planning, and minimal training and mentoring related to open modules. These conditions can impact the quality of classroom learning. Therefore, a thorough understanding of the concepts, functions, and steps involved in developing lesson plans and open modules is essential. With proper lesson planning, teachers can create a more focused and effective learning process that supports the achievement of educational goals in accordance with the applicable curriculum.